Parvovirus B19 Infection in Pregnancy-Course of the Disease, Fetal Complications and Management Tools: A Case Series and Literature Review - Olga Olejniczak; Jakub Kornacki; Daniel Boroń; Paweł Gutaj; Rafał Iciek; Ewa Wender-Ożegowska (MDPI AG, 2024)
Parvovirus B19 is a virus that causes a common and usually harmless infection in both children and adults. If the virus is transmitted transplacentally during pregnancy, it can have serious consequences for both the pregnant woman and the fetus. Potential complications include severe fetal anemia, which can lead to intrauterine fetal death. A common ultrasound finding in fetuses affected by parvovirus B19 is fetal edema, which is associated with a poor prognosis. Additionally, a rare but serious complication in pregnant women with parvovirus B19 infection is mirror syndrome. The diagnosis of parvovirus B19 infection during pregnancy necessitates close monitoring of the fetal condition. If fetal anemia is suspected, intrauterine transfusion is indicated to increase fetal survival. This study presents eight cases of parvovirus B19 infection in pregnant women, highlighting the various maternal-fetal complications encountered, along with diagnostic and treatment strategies.